2020
DOI: 10.1093/icvts/ivaa217
|View full text |Cite
|
Sign up to set email alerts
|

Repair of traumatic ventricular septal defect and left ventricular aneurysm after blunt chest trauma

Abstract: Blunt chest trauma can cause a variety of cardiac injuries, either immediately or days after the trauma. We report a case of traumatic ventricular septal defect and ribbonlike left ventricular aneurysm, which was diagnosed 15 years after the initial blunt chest trauma. It was successfully repaired using the endoventricular patch technique with a satisfactory 1-year follow-up result.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
2
0
1
Order By: Relevance
“…The self-healing rate of APVSD was high, but its mechanism is still unclear. Study had shown that inflammatory responses may be involved in this process [2][3][4]. In this study, in order to study the role of IL-1β, IL-6, TGF-β, and TNF-α in the formation of APVSD, children with APVSD who were surgically treated in the First Hospital of Hebei Medical University and Anhui Children's Hospital were selected.…”
Section: Introductionmentioning
confidence: 99%
“…The self-healing rate of APVSD was high, but its mechanism is still unclear. Study had shown that inflammatory responses may be involved in this process [2][3][4]. In this study, in order to study the role of IL-1β, IL-6, TGF-β, and TNF-α in the formation of APVSD, children with APVSD who were surgically treated in the First Hospital of Hebei Medical University and Anhui Children's Hospital were selected.…”
Section: Introductionmentioning
confidence: 99%
“…3 The post-traumatic ventricular aneurysm is caused by either a myocardial contusion or ischemia due to trauma-induced thrombosis. 4,5 In our case, considering the tear of the septal branches, we suppose that the detachment of the IVS from the apical wall caused by mechanical compression was the primary lesion, which was followed by the aneurysmal dilatation of the injured apical wall.…”
Section: Discussionmentioning
confidence: 76%
“…Серед кардіальних причин розвитку аневризм лівого шлуночка (АЛШ) окрім трансмурального інфаркту міокарда виявляють фістули коронарних артерій, інтрамуральний хід коронарних артерій, гі-пертрофічну кардіоміопатію, міокардит, аритмогенну кардіоміопатію правого шлуночка [1,2,3]. У літературі представлено поодинокі випадки виникнення АЛШ на тлі системних захворювань: інфекційного генезу (хвороба Чагаса, хвороба Бехчета, туберкульоз), сполучної тканини (системний червоний вовчак, саркоїдоз), хвороб накопичення глікогену, синдрому гіперімуноглобуліну Е, а також формування АЛШ унаслідок травми грудної клітки [1,[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. АЛШ у військовослужбовців є результатом несвоєчасної реваскуляризації інфаркт-залежної артерії [18], вогнепального поранення серця [19], травми грудної клітки [2,20].…”
unclassified